Analisis Kesiapan UMKM dalam Implementasikan SAK EMKM: Studi Kasus UMKM Mitra Alfamart di Karawang - Resdita Fery Atikasuri; Rohma Septiawati; Ihsan Nasihin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of MSMEs is very important for the progress of the Indonesian economy, however, MSMEs face several obstacles in their development, such as not having employees who are experts in their fields and lack of knowledge about how to make financial reporting in accordance with applicable standards (SAK EMKM). The purpose of this study is to determine whether Alfamart's partner MSMEs in Karawang are aware of the issuance of SAK EMKM, have adequate human resources, accrual basis accounting recording system, and whether they have adopted the concept of a business entity. Six business actors who work with Alfamart partners are the subjects of observation, interviews, and documentation in this study, which uses descriptive qualitative research methodology. The data analysis method developed by miles and huberman is data collection, data reduction, data presentation and conclusion drawing. Six different informants were used in source triagulation used for data validity testing. The results of the study state that the majority of business actors who work with alfamart partners are not ready to implement SAK EMKM. This is due to the lack of understanding in the accounting recording system in order to make financial records based on SAK EMKM and not knowing the issuance of SAK EMKM, not having adequate human resources, the accounting recording system applied is still on a cash basis not accrual basis and adopts the concept of a business entity.